Aging-dependent change in Th17 and cytokine response in multiple sclerosis - Wen Zhu; Shankar Revu; Chenyi Chen; Megan Dahl; Archana Ramkumar; Conor Kelly; Mandy J. McGeachy; Zongqi Xia (Journal of Neuroinflammation)
Abstract Background Multiple sclerosis (MS) is a chronic autoimmune disease damaging the central nervous system. Diminished inflammatory disease activity (DA) as people with MS (pwMS) age motivated randomized clinical trials assessing disease-modifying therapy (DMT) discontinuation in older pwMS given the concern for risks outweighing benefits. This study aims to examine whether peripheral production of Myelin Basic Protein (MBP)-driven cytokine responses mediate the aging-associated decline in MS inflammatory DA. Methods We included the clinical data of 669 adult pwMS between 2017 and 2022 who enrolled in a clinic-based prospective cohort. From a subset of 80 participants, we isolated fresh peripheral blood mononuclear cells (PBMCs) and cultured with 50 µg/ml of MBP (or heat-killed Candida) for 24 h. We assayed cell culture supernatants for interleukin 17 (IL-17) and interferon gamma (IFN-γ) using Enzyme-Linked Immunosorbent Assay and a subset of the supernatant samples using a commercial human cytokine/chemokine array. We examined the associations between age and annualized relapse rate (ARR) as well as between age and MBP-stimulated cytokine production (by cultured PBMC) using covariate-adjusted linear regressions. We performed mediation analyses to determine the extent to which MBP-driven cytokine response drives the association between age and ARR. Results Among 669 pwMS (mean age 51.7 ± 12.7 years, 80.7% women, 89.4% non-Hispanic White), ARR declined with age (β=-0.003, p < 0.001). Among the subgroup of 80 pwMS whose cultured PBMCs underwent ex vivo MBP stimulation, IL-17 production declined with age in women (β=-0.27, p = 0.04) but not men (β=-0.1, p = 0.73). MBP-driven IL-17 response partially mediated the association between older age and lower ARR (24.6% in women, 15.3% in men). In exploratory analyses, older pwMS (≥ 50 years) had marginally lower (IL-4, MCP-2, MCP-3, PDGF-AA, PDGF-AB/BB) and higher (Fractalkine, MDC) concentrations of several cytokines than younger pwMS (< 50 years), while certain cytokines (MCP-2, MDC) mediated whereas others negated the effect of age on ARR. Conclusion Diminished peripheral IL-17 response as a potential biological mechanism underlying the aging-dependent decline in MS inflammatory DA warrants further investigation.